2014
DOI: 10.1136/tobaccocontrol-2014-051977
|View full text |Cite
|
Sign up to set email alerts
|

Smokers' sensory beliefs mediate the relation between smoking a light/low tar cigarette and perceptions of harm

Abstract: Background The sensory belief that ‘light/low tar’ cigarettes are smoother can also influence the belief that ‘light/low tar’ cigarettes are less harmful. However, the ‘light’ concept is one of several factors influencing beliefs. No studies have examined the impact of the sensory belief about one’s own brand of cigarettes on perceptions of harm. Objective The current study examines whether a smoker’s sensory belief that their brand is smoother is associated with the belief that their brand is less harmful a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 26 publications
2
5
0
Order By: Relevance
“…In line with previous research [ 2 , 3 , 9 , 13 16 ], we also found that the belief that “light” cigarettes were smoother on the throat and chest was significantly associated with the belief that “light” cigarettes are less harmful. In fact, smokers who believed that “light” cigarettes are smoother on the throat and chest had 45 times greater odds of also believing that “light” cigarettes are less harmful and deliver less tar (36 % vs. 2 %).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In line with previous research [ 2 , 3 , 9 , 13 16 ], we also found that the belief that “light” cigarettes were smoother on the throat and chest was significantly associated with the belief that “light” cigarettes are less harmful. In fact, smokers who believed that “light” cigarettes are smoother on the throat and chest had 45 times greater odds of also believing that “light” cigarettes are less harmful and deliver less tar (36 % vs. 2 %).…”
Section: Discussionsupporting
confidence: 92%
“…The additional filter ventilation dilutes tobacco smoke with clean air, giving “light” cigarettes a weaker taste and causing less irritation to the throat and chest when smoked [ 1 4 ]. Previous research has shown that this smoothness sensation is associated with the belief of less harmfulness [ 2 , 13 16 ]. A study that included smokers from Canada, USA, UK, and Australia found that the majority of smokers believed that “light” cigarettes are smoother on the throat and chest than regular cigarettes, and this was strongly correlated with the belief that these cigarettes had lower health risks [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…These findings are novel because they experimentally demonstrate how sensory perceptions interact with beliefs to influence behavior. Cross-sectional studies (Elton-Marshall et al, 2015; Green et al, 2015; Mutti et al, 2011; O’Connor et al, 2013) indicate that sensory perceptions of a “weaker/lighter” taste reinforce smokers’ beliefs about “light” cigarettes and PREPs; we thus expected false beliefs and consumption to be positively associated among smokers providing lower strength and taste ratings. Instead these associations occurred among smokers who provided greater ratings, and were inverse or nonexistent among smokers providing lower ratings.…”
Section: Discussionmentioning
confidence: 96%
“…For example, in addition to their misleading marketing, “light” cigarettes contained filter-ventilation that produced sensory perceptions of a “lighter” or “smoother” taste (Kozlowski and O’Connor, 2002; O’Connor et al, 2013), reinforcing smokers’ false beliefs about lower harm (Elton-Marshall et al, 2015; Green et al, 2015; Mutti et al, 2011). While smokers generally provide negative subjective ratings of RNC cigarettes (Benowitz et al, 2007, 2012; Mercincavage et al, 2016; Strasser et al, 2007), implying lower use likelihood, few studies have associated these ratings with subsequent smoking behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…In all six countries (including China), a very high proportion of tobacco users believe that tobacco products that are smoother are also less harmful. This very strong linkage between smoothness and perception of less harmfulness 2,25 has been found in every country where this relationship has been investigated. Additionally, our findings showed that although "lights" smokers who believed that "lights" are less harmful were more likely to believe that "lights" are smoother (80.4%), most "nonlights" smokers (81.2%) also held similar beliefs.…”
Section: Discussionmentioning
confidence: 99%